2019
DOI: 10.24252/bio.v7i1.6000
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Bioactive Compound from Endophytic Fungi Isolated from Red Ginger (Zingiber officinale var. rubrum) Utilizing Brine Shrimp Lethality Assay

Abstract: Red ginger (Zingiber officinale var. rubrum) has been proven to show anticancer activity. Direct use bioactive compound from red ginger has many obstacles such as large amount of red ginger’s rhizome needed, limitation of planting area, and very long time of harvesting. Utilization of endophytic fungi from red ginger’s rhizome could be an alternative to the problems. The aims of this study were to determine bioactive compound produced by endophytic fungi and toxicity activity based on LC50. Endophytic fungi we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(26 reference statements)
0
2
0
2
Order By: Relevance
“…Upon 24 hours of treatment, Artemia salina larvae with LC 50 ; if the sample extract is LC 50 < 1 000 μg/mL, its toxicity is high, and the cytotoxicity is expected to occur. The level of toxicity would have an anticancer effect on extracts (Prasetyo et al, 2019). Evaluating the efficiency of hatching cysts concerning the time of exposure showed that extracts had notable hatching success after 36-48 hours, which would be the greatest hatching time for brine shrimp (Meyer et al, 1982;Braguini, Pires, & Alves, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon 24 hours of treatment, Artemia salina larvae with LC 50 ; if the sample extract is LC 50 < 1 000 μg/mL, its toxicity is high, and the cytotoxicity is expected to occur. The level of toxicity would have an anticancer effect on extracts (Prasetyo et al, 2019). Evaluating the efficiency of hatching cysts concerning the time of exposure showed that extracts had notable hatching success after 36-48 hours, which would be the greatest hatching time for brine shrimp (Meyer et al, 1982;Braguini, Pires, & Alves, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Meyer et al (1982) identified the brine shrimp lethality bioassay (BSLA) as a particular test that was able to detect screening the range of crude plant extracts in herbal medicine for cytotoxicity in a simple, quick and extensive bioassay for bioactive compounds of natural product (Meyer et al, 1982;Karchesy et al, 2016;Henry, 2017). The brine shrimp lethality test (BSLT) is the primary anticancer test process (Prasetyo, Sidharta, Hartini, & Mursyanti, 2019). However, there is a significant correlation between BSLT toxicity and cytotoxicity in certain cell lines, but this approach is not unique to anticancer activity (Asnaashari et al, 2017).…”
mentioning
confidence: 99%
“…Kelompok senyawa flavonoid memiliki mekanisme antibakteri dengan metode pengikatan adhesin permukaan sel bakteri sehingga gaya adhesi pada bakteri dan inang berkurang (Rosalina dkk., 2018). Prasetyo et al (2019) menemukan dua isolat jamur endofit yang diisolasi dari jahe merah (Z. officinale) mampu untuk menghasilkan flavonoid. Flavonoid dihasilkan oleh jamur endofit melalui jalur asam sikimat yang dimulai dengan proses kondensasi antara fosfoenolpiruvat (PEP) dan eritrosa-4-fosfat.…”
Section: Curcuma Dan Zingiberunclassified
“…Flavonoid dihasilkan oleh jamur endofit melalui jalur asam sikimat yang dimulai dengan proses kondensasi antara fosfoenolpiruvat (PEP) dan eritrosa-4-fosfat. Jalur asam sikimat memproduksi chorismate yang akan menjadi precursor untuk fenilalanin dan menjadi prekursor flavonoid (Prasetyo et al, 2019). Namun, beberapa senyawa antibakteri telah diidentifikasi secara spesifik pada jamur endofit di tanaman Curcuma dan Zingiber yang dinyatakan dalam Tabel 1.…”
Section: Curcuma Dan Zingiberunclassified